2008
DOI: 10.1128/iai.00827-08
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Intestinal Nematode Infection Exacerbates ExperimentalSchistosoma mansoniInfection

Abstract: Mixed-parasite infections are common in many parts of the world, but little is known of the effects of concomitant parasite infections on the immune response or on disease progression. We have investigated the in vivo effects of a chronic gastrointestinal nematode infection on the infectivity and development of the immune response against the common trematode helminth Schistosoma mansoni. The data show that mice carrying an established chronic Trichuris muris infection and coinfected with S. mansoni, had signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 50 publications
(61 reference statements)
0
16
0
Order By: Relevance
“…A chronic Trichuris muris infection within the large intestine enhanced the survival and migration of S. mansoni schistosomula to the portal system. Consequently, schistosome worm and egg burdens and associated pathology were enhanced when compared to mice infected with S. mansoni alone ( 34 ). This suggests that the immunomodulatory effects elicited in the mucosa of the large intestine to enable the gastrointestinal helminth to establish chronic infection can extend to other host tissues.…”
Section: Trematodes (Flukes)mentioning
confidence: 99%
“…A chronic Trichuris muris infection within the large intestine enhanced the survival and migration of S. mansoni schistosomula to the portal system. Consequently, schistosome worm and egg burdens and associated pathology were enhanced when compared to mice infected with S. mansoni alone ( 34 ). This suggests that the immunomodulatory effects elicited in the mucosa of the large intestine to enable the gastrointestinal helminth to establish chronic infection can extend to other host tissues.…”
Section: Trematodes (Flukes)mentioning
confidence: 99%
“…There are insufficient studies on the interactions of trichuriasis and schistosomiasis, specifically on the influence of co-infection on Schistosoma mansoni egg-induced hepatopathology. Others have found that concomitant infections of Schistosoma japonicum and Trichuris significantly increased the odds of anemia in children [4] and that mice with established chronic Trichuris muris infection and challenged with S. mansoni developed significantly higher S. mansoni worm burden and egg and granuloma burden in the liver [5]. To prepare for deployment of interventions such as vaccines against schistosomiasis [6], it is critical to understand the interactions between potential confounding factors that will be present in endemic areas, such as polyparasitism.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of coinfection are clearly multi-faceted and not surprisingly the documented outcomes of these relationships vary such that infection with one parasite species may enhance (e.g., [ 3 , 4 , 5 ]), diminish (e.g., [ 6 , 7 ]), or not affect (e.g., [ 8 , 9 ]) the establishment or survival of another parasite species. How parasite species respond to the presence of each other varies tremendously [ 10 ] and may be influenced by the particular species involved, location of the parasites in the host, duration of coinfection [ 11 ], strain differences within a parasite species [ 12 ], or which parasite infects the host first [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%